2019
DOI: 10.1155/2019/3196283
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Cushing’s Syndrome Unveiling a Metastatic Parotid Carcinoma

Abstract: Introduction Adrenocorticotropic hormone (ACTH) ectopic production is a rare cause of Cushing syndrome (CS). The most commonly associated tumours are small-cell lung carcinoma along with bronchial and thymic carcinoids. To date, only 5 cases have been published in the literature featuring ectopic ACTH secretion from metastatic acinic cell carcinoma (ACC) of the parotid gland. We hereby describe a very uncommon case of ectopic CS (ECS) unveiling a metastatic parotid ACC. Case Presentation A 46-year-old man with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…[ 45 ] Castro Oliveira et al also reported positive radiotracer uptake in a right parotid gland ACC and liver metastasis on SSTR scintigraphy octreoscan. [ 46 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 45 ] Castro Oliveira et al also reported positive radiotracer uptake in a right parotid gland ACC and liver metastasis on SSTR scintigraphy octreoscan. [ 46 ]…”
Section: Discussionmentioning
confidence: 99%